Gut microbiome alterations during gastric cancer: evidence assessment of case–control studies - Zhang, Ruimin; Wu, Yingxin; Ju, Wantao; Wang, Senlin; Liu, Yanjun; Zhu, Hongmei (Frontiers in Microbiology, 2024)
The study aims to systematically identify the alterations in gut microbiota that observed in gastric cancer through comprehensive assessment of case-control studies.The systematic literature search of PubMed, Embase, Cochrane Library, and Web of Science was conducted to identify case-control studies that compared the microbiomes of individuals with and without gastric cancer. Quality of included studies was evaluated with the Newcastle-Ottawa Quality Assessment Scale (NOS). Meta-analyses utilized a random-effects model, and subgroup and sensitivity analyses were performed to assess study heterogeneity. All data analyses were performed using the "metan" package in Stata 17.0, and the results were described using log odds ratios (log ORs) with 95% confidence intervals (CIs).A total of 33 studies involving 4,829 participants were eligible for analysis with 29 studies provided changes in α diversity and 18 studies reported β diversity. Metaanalysis showed that only the Shannon index demonstrated statistical significance for α-diversity [-5.078 (-9.470, -0.686)]. No significant differences were observed at the phylum level, while 11 bacteria at genus-level were identified significant changed, e.g., increasing in Lactobacillus [5.474, (0.949, 9.999)] and Streptococcus [5.095, (0.293, 9.897)] and decreasing in Porphyromonas and Rothia with the same [-8.602, (-11.396, -5.808)]. Sensitivity analysis indicated that the changes of 9 bacterial genus were robust.Streptococcus in Koreans with gastric cancer, whereas those with gastric cancer from Portugal had a reduced Neisseria. Regarding the sample sources, the study observed an increase in Lactobacillus and Bacteroides in the gastric mucosa of people with gastric cancer, alongside Helicobacter and Streptococcus. However, the relative abundance of Bacteroides decreased compared to the non-gastric cancer group, which was indicated in fecal samples.This study identified robust changes of 9 bacterial genus in people with gastric cancer, which were country-/ sample source-specific. Large-scale studies are needed to explore the mechanisms underlying these changes.